The nature and origin of climatic fluctuations in Northeastern North America - Barry, R. (Géographie physique et Quaternaire, 1981)
Features of the atmospheric circulation and climate of northeastern Canada are reviewed. In particular, the role of the upper level trough and its variability are discussed. It is shown that longitudinal displacements of the mean summer trough create anomalies of both air temperature and sea ice conditions in the region of Baffin Island. Climatic anomaly patterns in Labrador-Ungava and Keewatin associated with trough displacements are also summarized. Two examples of the application of such information to paleoclimat-ological questions are discussed. One concerns the influx of "exotic" tree pollen into Baffin Island and its previously postulated relationship to southerly airflow. It is concluded that pollen peaks cannot yet be reliably used as a paleowind index. The pattern of glacial inception and ice sheet extension during the Last Glacial Maximum is also briefly considered in the light of the available climatic information. Finally, the role of orbital variations affecting the seasonal pattern of solar radiation is discussed with reference to the last glacial cycle.